2021
DOI: 10.1007/s10534-021-00305-0
|View full text |Cite
|
Sign up to set email alerts
|

An update on magnesium and bone health

Abstract: In 2009 EFSA Panel concludes that a cause and effect relationship has been established between the dietary intake of magnesium (Mg) and maintenance of normal bone. After 2009, numerous studies have been published, but no reviews have made an update on this topic. So, the aim of this narrative review was to consider the state of the art since 2009 on relationship between Mg blood levels, Mg dietary intake and Mg dietary supplementation (alone or with other micronutrients; this last topic has been considered sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 36 publications
1
58
0
5
Order By: Relevance
“…It is known that magnesium plays a crucial role in bone health. A positive association between serum Mg, calcium, parathyroid hormone, and osteocalcin was found [ 28 ]. It is found that balancing calcium and magnesium is important to maintain optimal bone density.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that magnesium plays a crucial role in bone health. A positive association between serum Mg, calcium, parathyroid hormone, and osteocalcin was found [ 28 ]. It is found that balancing calcium and magnesium is important to maintain optimal bone density.…”
Section: Discussionmentioning
confidence: 99%
“…A link between magnesemia and fracture risk has been shown in the literature [137,138]. Lower-than-recommended daily Mg intake (265 mg/day in many studies) is linked to a lower bone mineral density, and a higher fracture risk is observed [133].…”
Section: Magnesium and Bonementioning
confidence: 96%
“…In humans, a few reviews have updated knowledge on Mg and bone health [5,132,133]. A recent narrative review [133] identified 28 studies since 2009 on the link between Mg and bone in adults, mostly postmenopausal women, considering blood Mg values, Mg intake, and Mg supplementation.…”
Section: Magnesium and Bonementioning
confidence: 99%
See 2 more Smart Citations